Powdery mildew on some non cucurbites cultivated crops from Khandesh region of Maharashtra state - P. Patil2, V. P. Pawar1* and Geeta (Journal of Experimental Sciences, 2011)
Powdery mildew on some non cucurbites cultivated crops from Khandesh region of Maharashtra state Ã‚Â 